Teacher EQ and burnout an intervention program - Lontiong, Danilyn Joy R. (2008)
This study intended to determine the relationship between EQ and teacher burnout, and to identify which among the 5 subscales of EQ predict burnout behavior. It also sought to find out the moderating variables that influence EQ and burnout behavior. Embedded mixed methods design was utilized in the study. The study involved 105 public elementary school teachers in Marikina City. The results indicate that EQ may be an avenue to combat teacher burnout and subsequently improve teaching performance and increase pupil learning outcomes. An intervention program based on self-understanding activities is effective in increasing the general mood EQ of teachers.